Molecular characterization of a new efficiently transducing bacteriophage identified in meticillin-resistant Staphylococcus aureus - Varga, Marian; Pantůček, Roman; Růžičková, Vladislava; Doškař, Jiří (Journal of general virology, 2016)
In Staphylococcus aureus, generalized transduction mediated by temperate bacteriophages represents a highly efficient way of transferring antibiotic resistance genes between strains. In the present study, we identified and characterized in detail a new efficiently transducing bacteriophage of the family Siphoviridae, designated ϕJB, which resides as a prophage in the meticillin-resistant S. aureus (MRSA) strain Jevons B. Whole-genome sequencing followed by detailed in silico analysis uncovered a linear dsDNA genome consisting of 43 ,12 bp and comprising 70 ORFs, of which ∼40 encoded proteins with unknown function. A global genome alignment of ϕJB and other efficiently transducing phages ϕ11, ϕ53, ϕ80, ϕ80α and ϕNM4 showed a high degree of homology with ϕNM4 and substantial differences with regard to other phages. Using a model transduction system with a well-defined donor and recipient, ϕJB transferred the tetracycline resistance plasmid pT181 and a penicillinase plasmid with outstanding frequencies, beating most of the above-mentioned phages by an order of magnitude. Moreover, ϕJB demonstrated high frequencies of transferring antibiotic resistance plasmids even upon induction from a lysogenic donor strain. Considering such transducing potential, ϕJB and related bacteriophages may serve as a suitable tool for elucidating the nature of transduction and its contribution to the spread of antibiotic resistance genes in naturally occurring MRSA populations.
Keywords: syntenie; Drug Resistance, Bacterial; bakteriální léková rezistence; Methicillin-Resistant Staphylococcus aureus; fylogeneze; transdukce genetická; Synteny; Microscopy, Electron, Transmission; přenos genů horizontální; Prophages; Virus Activation; Genome, Viral; pořadí genů; Open Reading Frames; Molecular Sequence Data; Gene Order; Sequence Homology; transmisní elektronová mikroskopie; methicilin rezistentní Staphylococcus aureus; Sequence Analysis, DNA; výpočetní biologie; plazmidy; Phylogeny; molekulární sekvence - údaje; aktivace viru; genom virový; Siphoviridae; sekvenční analýza DNA; Transduction, Genetic; otevřené čtecí rámce; Gene Transfer, Horizontal; DNA, Viral; Plasmids; Lysogeny; lyzogenie; Computational Biology; sekvenční homologie; profágy; DNA virů